POLITICAL CAMPAIGNING DURING PANDEMIC: GIBRANâ€™S POLITICAL BRAND ON INSTAGRAM DURING SOLO MAYORAL ELECTION 2020 - Irani; Wahyutama (Konvergensi, 2024)
The utilization of social media by politicians for political campaigns is increasingly common at the present time. Even more so during the pandemic in which the offline interaction between politicians and voters is severely limited. Thus, this research is interested in investigating the utilization of social media by a political candidate (Gibran Rakabuming) during the City Mayoral Election. This research aims to uncover the construct of the political brand displayed by Gibran on Instagram during the City Mayoral Election 2020 in Solo, Central Java. This research employs quantitative content analysis on social media contents posted by Gibran (on his official IG account @gibran_rakabuming) during the period of November 8, 2019 until May 31, 2021. From the total population of 2,031 posts, this research selected 90 posts (using non-probability purposive sampling) as samples. The research found: 1) the two elements of political brand dominantly displayed by Gibran on his Instagram account are integrity and competence. In addition, Gibran also displayed the element of social imagery by which he showcased his image as a young political candidate (or â€œmillennial generationâ€); 2) the element of political brand consistently displayed by Gibran was professionalism by which he highlighted his image as a successful entrepreneur; 3) Gibran was not sufficiently found to be using his social media account to develop interaction with his followers. The limitation of this research mainly comes from its sample size and sampling technique. This research utilizes non-probability sampling, which limits its external validity. Therefore, the findings of this research cannot be generalized to describe the total population (all social media content posted by Gibran during the election). However, this research provides a useful initial study on the strategy utilized by political candidates in Indonesia (through the use of social media) to win elections amid the limitations imposed by the pandemic. Keywords: Political Branding, Social Media, Gibran Rakabuming, Solo Mayoral Election 2020, Pandemic